Disease Lesion Mimicry Caused by Mutations in the Rust Resistance Gene rp1. - Hu, G. (1996)
The rp1 locus of maize controls race-specific resistance to the common rust fungus Puccinia sorghi. Four mutant or recombinant Rp1 alleles (rp1-NC3, Rp1-D21, Rp1-MD19, and Rp1-Kr1N) were identified. They condition necrotic phenotypes in the absence of the rust pathogen. These Rp1 lesion mimics fall into three different phenotypic classes: (1) The rp1-NC3 and Rp1-D21 alleles require rust infection or other biotic stimulus to initiate necrotic lesions. These alleles react strongly to all maize rust biotypes tested and also to nonhost rusts. (2) The Rp1-MD19 allele, which has a similar phenotype, also requires a biotic stimulus to initiate lesions. However, Rp1-MD19 shows the race specificity of the Rp1-D gene. (3) The Rp1-Kr1N allele specifies a diffuse necrotic phenotype in the absence of any biotic stimulus and a race-specific reaction when inoculated with maize rust.